Risk factors associated with suicidal ideation among cancer patients: a systematic review and meta-analysis - Chen, Jie; Ping, Zhiheng; Hu, Deying; Wang, Jiaqing; Liu, Yilan (Frontiers in Psychology, 2024)
Objective The objective of this review was to provide a comprehensive summary and analysis of the risk factors associated with suicidal ideation among cancer patients. Methods This review adhered to the PICO/S framework and guidelines outlined in the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) framework (PROSPERO CRD42023433639). We searched Web of Science, PubMed, Embase, Scopus, PsycINFO, and Cochrane Library from the establishment date of the databases until June 9, 2023 for observational studies that reveal risk factors associated with suicidal ideation among cancer patients. Software Review Manager 5 (vision 5.4) was used for Meta-analyses. Results 4,921 studies were obtained through the search of the databases, 40 of which were eligible. Meta-analysis revealed that suicidal ideation in cancer patients was significantly associated with marital status, living alone, post-traumatic stress disorder (PTSD), panic disorder, education, psychiatric illness history, social functioning, childhood adversity experience, financial problems, pain, depression, demoralization, vomiting, residence and anxiety. Conclusion Being unmarried, living alone, less educated, living in rural, financial problems, pain, vomiting, PTSD, psychiatric illness history, lower social functioning, childhood adversity experience, anxiety, depression, demoralization, panic disorder were risk factors for suicidal ideation among cancer patients. This review provided evidence-based information for identifying and reducing the risk of suicide in cancer survivors. Systematic review registration: https://www.crd.york.ac.uk/PROSPERO/, CRD42023433639.